The epidemiology of amyloidosis in Queensland, Australia. (31st May 2019) - Wisniowski, Brendan; McLeod, Donald S. A.; Adams, Rebecca; Harvey, Yasmin; Brown, Ian; McGuire, Lloyd; Armes, Jane; Mollee, Peter
Summary: Published studies on the epidemiology of amyloidosis have relied on death certificate data for case ascertainment. We estimated the incidence and mortality burden of amyloidosis among residents of the Australian state, Queensland, aged ≥20 years for the years 1999–2013 based on case ascertainment from histopathology reports. Information systems for participating laboratories were scrutinised to identify histopathology reports that documented a diagnosis of amyloidosis. Case mortality status was determined via linkage to the National Death Index. A total of 447 cases of amyloidosis were identified, with a median age at diagnosis of 66 years. A plasma cell dyscrasia was identified in 72% of patients who had paraprotein studies performed. The estimated incidence for Queenslanders aged ≥20 years was 12·1 cases per million person years. The median survival was 2·45 years. Age at diagnosis, presence of a paraprotein, earlier year of diagnosis, and inner regional location of residence (compared with residence in a major city) were independently associated with reduced survival. Our data confirms previously reported incidence data for amyloidosis of approximately 10 cases per million patient years and indicates that survival for Queensland patients with amyloidosis is improving, though it remains poor for the elderly and patients with AL amyloidosis.